Transport, Fate and Impacts of the Deep Plume of Petroleum Hydrocarbons Formed During the Macondo Blowout - Bracco, Annalisa; Paris, Claire B.; Esbaugh, Andrew J.; Frasier, Kaitlin; Joye, Samantha B.; Liu, Guangpeng; Polzin, Kurt L.; Vaz, Ana Carolina (Frontiers in Marine Science, 2020)
The 2010 Macondo oil well blowout consisted in a localized, intense infusion of petroleum hydrocarbons to the deep waters of the Gulf of Mexico. A substantial amount of these hydrocarbons did not reach the ocean surface but remained confined at depth within subsurface plumes, the largest and deepest of which was found at ∼ 1000–1200 m of depth, along the continental slope (the deep plume). This review outlines the challenges the science community overcame since 2010, the discoveries and the remaining open questions in interpreting and predicting the distribution, fate and impact of the Macondo oil entrained in the deep plume. In the past 10 years, the scientific community supported by the Gulf of Mexico Research Initiative (GoMRI) and others, has achieved key milestones in observing, conceptualizing and understanding the physical oceanography of the Gulf of Mexico along its northern continental shelf and slope. Major progress has been made in modeling the transport, evolution and degradation of hydrocarbons. Here we review this new knowledge and modeling tools, how our understanding of the deep plume formation and evolution has evolved, and how research in the past decade may help preparing the scientific community in the event of a future spill in the Gulf or elsewhere. We also summarize briefly current knowledge of the plume fate – in terms of microbial degradation and geochemistry – and impacts on fish, deep corals and mammals. Finally, we discuss observational, theoretical, and modeling limitations that constrain our ability to predict the three-dimensional movement of waters in this basin and the fate and impacts of the hydrocarbons they may carry, and we discuss research priorities to overcome them.